A Challenge of Vocational Education for Preparing Green Employment - Asnawi, Rustam; Djatmiko, I (INVOTEC, 2015)
Currently the vocational education has been oriented to the educational processes in which focusing on the development of the student in order to ready to work professionally and ready to improve their self-potential in particular field work. Meanwhile, today and future jobs in various business sectors and industry are still growing and developing towards green jobs. If there is no counter and solution for this growth of green jobs, then it would create a new gap between the output’s competencies of vocational education and the qualification that needed by various business sector and industry. After studying some latest literatures, it was found that there is no any explicitly and concretely both concept and definition of green jobs in the vocational education curriculum (Curriculum 2013). Thus, this paper presents the urgent and such a challenge to change the philosophy of vocational education towards green jobs and ecology oriented.